Analisis Akuntabilitas Dan Tranparansi Pengelolaan Dana Bantuan Operasional Sekolah Di MTs Nurhasanah Balai Jaya - Hasanah Azizi; Fauzi Arif Lubis; Laylan Syafina (Shofanah Media Berkah, 2023)
This research is a research with a descriptive approach method and a type of qualitative research conducted at MTs Nurhasanah Balai Jaya. This study aims to determine how to implement accountability and transparency in the management of School Operational Assistance (BOS) funds in 2022. The benefit of this study is to find out whether MTs Nurhasanah has implemented accountability and transparency in managing BOS funds in 2022. The data collection methods used were interviews, observations, and documentation studies. In this study, researchers interviewed several resource persons, namely: School Principal, Treasurer, Administration Staff, School Operators, Teachers and Parents. The results show that the implementation of the principles of accountability and management of BOS funds at MTs Nurhasanah Balai Jaya has been running well in accordance with the BOS 2022 technical guidelines, accountability of BOS funds is carried out every semester, but the implementation of transparency has not run well as shown by the absence of socialization about the planning and use of BOS funds to parents/guardians of students and the absence of installation on information boards regarding the realization of the use of BOS funds.